Diagnostic Accuracy of Office Blood Pressure Measurement and Home Blood Pressure Monitoring for Hypertension Screening Among Adults: Results From the IDH Study - Hiroyuki Mizuno; Eunhee Choi; Kazuomi Kario; Paul Muntner; Chloe L. Fang; Justin Liu; Dona N. Sangapalaarachchi; Michael Lam; Yuichiro Yano; Joseph E. Schwartz; Daichi Shimbo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Using high awake blood pressure (BP; ≥130/80 mm Hg) on ambulatory BP monitoring (ABPM) as a reference, the purpose of this study was to determine the accuracy of high office BP (≥130/80 mm Hg) at an initial visit and high confirmatory office BP (≥130/80 mm Hg), and separately, high home BP (≥130/80 mm Hg) among participants with high office BP (≥130/80 mm Hg) at an initial office visit. Methods and Results The accuracy of office BP measurements using the oscillometric method for detecting high BP on ABPM was determined among 379 participants with complete office BP and ABPM data in the IDH (Improving the Detection of Hypertension) study. For detecting high BP on ABPM, the accuracy of high confirmatory office BP using the oscillometric method and, separately, high home BP was also determined among the subgroup of 122 participants with high office BP at an initial visit and complete home BP monitoring data. High office BP had moderate sensitivity (0.61 [95% CI, 0.53–0.68]) and high specificity (0.85 [95% CI, 0.80–0.90]) for high awake BP. High confirmatory office BP and high home BP had moderate sensitivity (0.69 [95% CI, 0.59–0.79] and 0.79 [95% CI, 0.71–0.87], respectively) and low and moderate specificity (0.44 [95% CI, 0.27–0.61] and 0.72 [95% CI, 0.56–0.88], respectively). Conclusions Many individuals with high BP on ABPM do not have high office BP. Confirmatory office BP and home blood pressure monitoring also had limited ability to identify individuals with high BP on ABPM.